Fat cells reactivate quiescent neuroblasts via TOR and glial insulin relays in Drosophila - Sousa-Nunes, Rita; Yee, Lih Ling; Gould, Alex P. (Nature (London), 2011)
Nerve progenitors hungry for action The availability of nutrients prompts quiescent neural stem cells (neuroblasts) in Drosophila larvae to begin to divide. A study of the mechanism linking diet to stem-cell behaviour has identified a relay mechanism regulating this nutritional checkpoint. Specific insulin-like peptides produced within the brain by glia — non-neuronal cells with various physical and biochemical support roles — form a bridge from the amino-acid/TOR-dependent signal derived from the fat body to PI3K/TOR signalling in neuroblasts to induce exit from quiescence. Little is known about how nutritional cues are detected by quiescent neural stem cells (neuroblasts in Drosophila melanogaster ) and how these signals are relayed to reactivate their cell cycle to exit quiescence. This study uses an integrative physiology approach to identify the relay mechanism regulating this nutritional checkpoint in neural progenitors. It is found that specific insulin-like peptides produced within the brain by glia bridge the amino-acid/TOR-dependent signal derived from the fat body with PI3K/TOR signalling in neuroblasts to induce exit from quiescent. Many stem, progenitor and cancer cells undergo periods of mitotic quiescence from which they can be reactivated 1 , 2 , 3 , 4 , 5 . The signals triggering entry into and exit from this reversible dormant state are not well understood. In the developing Drosophila central nervous system, multipotent self-renewing progenitors called neuroblasts 6 , 7 , 8 , 9 undergo quiescence in a stereotypical spatiotemporal pattern 10 . Entry into quiescence is regulated by Hox proteins and an internal neuroblast timer 11 , 12 , 13 . Exit from quiescence (reactivation) is subject to a nutritional checkpoint requiring dietary amino acids 14 . Organ co-cultures also implicate an unidentified signal from an adipose/hepatic-like tissue called the fat body 14 . Here we provide in vivo evidence that Slimfast amino-acid sensing and Target of rapamycin (TOR) signalling 15 activate a fat-body-derived signal (FDS) required for neuroblast reactivation. Downstream of this signal, Insulin-like receptor signalling and the Phosphatidylinositol 3-kinase (PI3K)/TOR network are required in neuroblasts for exit from quiescence. We demonstrate that nutritionally regulated glial cells provide the source of Insulin-like peptides (ILPs) relevant for timely neuroblast reactivation but not for overall larval growth. Conversely, ILPs secreted into the haemolymph by median neurosecretory cells systemically control organismal size 16 , 17 , 18 but do not reactivate neuroblasts. Drosophila thus contains two segregated ILP pools, one regulating proliferation within the central nervous system and the other controlling tissue growth systemically. Our findings support a model in which amino acids trigger the cell cycle re-entry of neural progenitors via a fat-body–glia–neuroblasts relay. This mechanism indicates that dietary nutrients and remote organs, as well as local niches, are key regulators of transitions in stem-cell behaviour.